2018
DOI: 10.2166/wp.2018.129
|View full text |Cite
|
Sign up to set email alerts
|

Rural water supply in Nigeria: policy gaps and future directions

Abstract: The alarming state of safe water deprivation among the residents of rural communities in Nigeria is well recognized. Unfortunately, research that shows the policy gaps in the water supply sector of the country and measures to eliminate them in order to improve water supply sustainability in the country is lacking. This paper investigates the landscape of water service provision to rural communities in Nigeria using investigative and qualitative approaches due to the desire to explore the experience and opinion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Nevertheless, this management model has exhibited several weaknesses which have been explored in scientific literature for several decades. Some authors observed that the lack of institutional support and political planning are major contributors to systems' failures, as seen in Ghana [5] and Nigeria [12]. Insufficient financial resources and weak tariff schemes also have been recognized as leading causes of failure of rural water services [8,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this management model has exhibited several weaknesses which have been explored in scientific literature for several decades. Some authors observed that the lack of institutional support and political planning are major contributors to systems' failures, as seen in Ghana [5] and Nigeria [12]. Insufficient financial resources and weak tariff schemes also have been recognized as leading causes of failure of rural water services [8,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient financial resources and weak tariff schemes also have been recognized as leading causes of failure of rural water services [8,[13][14][15]. Additionally, several studies identified maintenance issues as critical to the functionality of community-managed systems, such as the execution of insufficient preventive repairs [16], difficulties to obtain spare parts [12] and lack of technical support from external entities [17,18]. Therefore, community management models of water supply require further commitment from multiple stakeholders in order to achieve better results and benefit a larger number of people [19].…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 46 percent of water schemes (water schemes are water supply projects with drinking water as the main water component) are non-functional in Nigeria [84]. The failure of these utilities impacts water access geographically, manifestly in the ruralurban dichotomies and differences [108,110] and at the household level [111]. In addition, existing water infrastructure cannot sustain current population growth due to the rate of infrastructural deterioration and low infrastructural investment [86].…”
Section: Infrastructure Failures and Sustainabilitymentioning
confidence: 99%
“…This is a participatory approach, i.e., the target community is responsible for operating, maintaining and managing the water plants, built with assistance of external actors that must provide constant financial, technical, institutional and political support to guarantee the systems' functionality (Kleemeier, 2000;Whittington et al, 2009;Hunter et al, 2010;Hutchings et al, 2015;Behnke et al, 2017). This tactic has been employed in many countries around the world, namely Brazil, Chile, Peru, Finland, Nepal and Nigeria (Heller and Pádua, 2006;Whittington et al, 2009;Opare, 2011;Borja-Vega et al, 2017;Calzada et al, 2017;Chukwuma, 2018;Rautanen and White, 2018). Among them, both successes and failures have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Rautanen and White (2018) demonstrated a successful case in Nepal, where a combination of community engagement and financial transparency were deemed key factors to the sustainability of this model. Chukwuma (2018) presents case studies in Nigeria, where community management could not improve communities' quality of life due to weak institutional and political support. In the same way, Harvey and Reed (2007) observed that governmental policies were responsible for creating a scenario of isolation of rural communities through weak political representation, which contributed to several failures in water supply systems in Africa.…”
Section: Introductionmentioning
confidence: 99%